Speech bandwidth extension using time-domain data hiding - Phaneendra KURADA , Sailaja MARUVADA , Koteswara Rao SANAGAPALLEA (International Journal of Advanced Science and Technology, 2020)
A novel time-domain speech bandwidth extension algorithm is proposed to transmit information about the missing speech frequencies over a hidden channel, i.e., the related encoded spectral envelope parameters are hidden within the narrowband speech signal using time-domain data hiding technique. The hidden information is recovered reliably at the receiver to produce a wideband speech signal of much higher quality. Obtained results confirm the excellent reconstructed wideband speech quality of the proposed method over traditional methods.